Analysis of The Causes of The Disintegration of The Government of The Abbasiyah Dynasty (1000 M-1250 M) - Esa Prasastia A, Muhammad; Rofiq, Abdul (Green Publisher, 2022)
This article will explore why and what factors led to the decline of the Abbasid dynasty after the first period. This research is motivated by the historical fact that in the second period, the glorious period and the ideal government that had been built by the predecessors gradually degraded until finally this dynasty collapsed. One of the causes is none other than disintegration. This article aims to review several things related to how the consolidation and disintegration of the Abbasid dynasty was? And also the factors causing the disintegration of the Abbasid dynasty? The research findings show that the disintegration of the abbasiyah dynasty (1000-1250) AD was caused by none other than two factors, namely internal factors such as loss of social solidarity, extent of power, competition between institutions. Meanwhile, external factors were caused by, among others, Byzantine attacks, coalition crusades.